Study on hepatoprotective effect of root methanolic extract of Acanthus ilicifolius L. in carbon tetrachloride induced mice - Định, Phan Kim; An, Trương Đình Yến; Trúc, Trương Thị Thanh; Trang, Đái Thị Xuân (Vietnam Journal of Biotechnology, 2016)
Acanthus ilicifolius is a common medicinal herb used in treatment for hepatic diseases in Vietnamese traditional medicine. This study investigated hepatoprotective effects of methanol extract of A.ilicifolius roots at various concentrations on mice having carbon tetrachloride (CCl4)-induced liver damages by measuring levels of two liver enzymes (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)). Mice’s livers were injured by using CCl4 in olive oil, in the ratio of 1 to 4 with the dosing concentration of 0.2 ml per day in 4 consecutive weeks (or 8 consecutive weeks). After one hour taking CCl4 by oral administration, mice were treated with roots’ methanol extract at three different concentrations (15, 30, and 45 mg/kg BW). Silymarin, a commercial liver protector was used as a positive control. After 4 weeks of treatment, the AST levels decreased by 86.6%, 86.3%, 85.3% and ALT levels declined by 83.9%, 83.8%, 81.4%. After 8 weeks of treatment, the use of 30 mg/kg BW root extract showed the best hepatoprotective activity with the lowest levels of AST and ALT. Our result also indicated that the hepatoprotective effects of roots’ methanol extract of A.ilicifolius were similar to that of sylimarin (using at 16 mg/kg BW). The microscopic structure proved that the hepatocytes recovered significantly in mice treated with roots’ methanol extract of A.ilicifolius at dose 45 mg/kg BW. However, root extract of A.ilicifolius at dose of 15 and 30 mg/kg BW could not improved liver damages comparing to untreated mice. The qualitative analysis of phytochemical compounds showed that Acanthus ilicifolius root contains alkaloid, flavonoid, triterpenoid, steroid, glycoside, and phenol substances.